Exploring the Implementation of Project-Based Learning in Arabic Language Education under the "Kurikulum Merdeka" - Muhammad Ihsan; M. Abdul Hamid; Nur Hasan; Syarifaturrahmatullah (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
The "Kurikulum Merdeka" is a curriculum that emphasizes flexibility, innovation, and student-centered learning. Implementing project-based learning (PjBL) in this curriculum is one way to improve students' Arabic language skills. This study aims to explore the implementation of PjBL in the "Kurikulum Merdeka" for Arabic language learning and the factors influencing it at MAN 2 Kutai Kartanegara. This study uses a qualitative approach with a case study method. Data was collected through observation, interviews with teachers and students, and documentation of learning tools. The data obtained were analyzed using Miles and Huberman's theory, which consists of data collection, condensation, presentation, and conclusion drawing. The results of this study indicate that PjBL is implemented through various projects, with the most commonly implemented being conversation videos and news reading videos. The implementation process consists of planning, monitoring, and evaluation stages. Supporting factors include student enthusiasm and the role of teachers as facilitators in providing freedom and guidance. At the same time, the obstacle is the difference in students' backgrounds, which affects their Arabic language skills. It can be concluded that implementing PjBL is a learning strategy to improve students' Arabic language skills, especially in terms of fluency, accuracy, and content in line with the "Kurikulum Merdeka" principles.